2010
DOI: 10.1007/s00192-010-1235-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimum 6-year outcomes for interstitial cystitis treated with sacral neuromodulation

Abstract: With a minimum 6-year follow-up we determined that sacral neuromodulation provides adequate improvement for the symptoms of recalcitrant interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…No RCTs have been completed to assess the effect of SNM on symptoms of IC/BPS. However, multiple observational studies have been reported, [188][189][190][191][192][193][194][195] including long-term followup of 86 ± 9.8 months. 191 All studies include patients refractory to multiple IC/BPS treatment options.…”
Section: Sacral Neuromodulation (Snm) (Option Grade C)mentioning
confidence: 99%
See 1 more Smart Citation
“…No RCTs have been completed to assess the effect of SNM on symptoms of IC/BPS. However, multiple observational studies have been reported, [188][189][190][191][192][193][194][195] including long-term followup of 86 ± 9.8 months. 191 All studies include patients refractory to multiple IC/BPS treatment options.…”
Section: Sacral Neuromodulation (Snm) (Option Grade C)mentioning
confidence: 99%
“…There is a surgical revision rate of 27-50%. 189,191 Guideline: Based on consistent Level 3 evidence, SNM may be offered as an option for the treatment of IC/BPS to patients who have symptoms refractory to multiple other treatments. Therapy is costly and not widely available at all centres.…”
Section: Sacral Neuromodulation (Snm) (Option Grade C)mentioning
confidence: 99%
“…Frequently, it resolves or reduces associated CPPS. Marinkovic et al [49] evaluated patients after implantation with InterStim (Medtronic, Fridley, MN) over a minimum 6-year follow-up and determined that SNS provides adequate improvement for the symptoms of refractory interstitial cystitis. Van Wunnik et al [50] used SNS for the treatment of chronic functional anorectal pain.…”
Section: Neurostimulationmentioning
confidence: 98%
“…Mean voided volume increased from 111 to 264 ml and pain decreased from 5.8 to 1.6 on a 0 to 10 visual analog pain scale. Another study with a follow-up of a mean of 86 months reported a 64% reduction of pain in 30 patients who underwent SNM [40]. SNM might be effective for treating neurogenic bladder patients, but, as in BPS, the level of evidence is low [41].…”
Section: Nonobstructive Chronic Underactive Bladdermentioning
confidence: 99%